ENZIM MANANASE DAN FERMENTASI JAMUR UNTUK MENINGKATKAN KANDUNGAN NUTRISI BUNGKIL INTI SAWIT PADA PAKAN IKAN NILA BEST (Oreochromis niloticus) - Bakara, Okta; Santoso, Limin; Heptarina, Deisi (Aqusains: Jurnal Ilmu Perikanan dan Sumberdaya Perairan, 2013)
Palm kernel meal is CPO (Crude Palm Oil)-by product are potentially as an alternative raw material fish feed. This research aims to know the influence of the enzyme mananase and mold fermentation to improve the quality of palm kernel over the extent of the digestibility of oreochromis BEST. This study used a Randomized Complete design of experiment method (RAL) with seven treatments and three replicates each. BEST tilapia with weights 25 ± 1.57 gram put in 21 60x40x40cm3 sized aquarium. Test feed was given for 15 days as a mortgage with a frequency three times a day. The results showed that the total digestibility (56,74%) and protein digestibility (82,38%) resulting from the best treatment of palm kernel with the addition of mananase enzyme and fermentation of the mold Rhizopus oligosporus and for carbohydrate digestibility (60,72%) and energy digestibility (71,82%) obtained the best result from the treatment of palm kernel with the addition of mananase enzyme and fermentation of Trichoderma reesei mould.